2022
DOI: 10.1177/23780231221110277
|View full text |Cite
|
Sign up to set email alerts
|

The Resonance of Repression: Moral Intuitions, Skepticism toward Racial Injustice, and Public Support for Trump’s “Law and Order” Response to the 2020 Racial Justice Protests

Abstract: The limited research on support for state repression of protests points to protest violence, ideological opposition, and racial/ethnic resentment, but few have examined how moral intuitions influence support for repression and racialized opposition to protest claims. The authors use a national survey of 1,030 respondents, fielded in June 2020 at the height of the post-Floyd Black Lives Matter protests, to investigate the moral motivations for supporting Trump’s “law and order” response. Drawing on moral founda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…It may be that conservatives—who tend to be supportive of police intervention broadly (e.g., Silver and Pickett 2015) and who are increasingly protective of free speech in a perceived “cancel culture” (e.g., Fahey, Roberts, and Utych 2023)—focused on the nature of the government intervention rather than the protest cause in evaluating the incidents. Along these lines, regarding support for police repression, conservatives may have been more likely than liberals to believe that the broader social system and its representatives (e.g., police) are just and that the repression of protests by police is justified to maintain social order (Goff et al 2022; Silver 2020; Silver, Goff, and Iceland 2022). Another possibility is that conservatives were less likely to view police presence as a form of repression, perhaps because policing of right-leaning protests is often less harsh than policing of left-leaning protests (e.g., Jackson 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It may be that conservatives—who tend to be supportive of police intervention broadly (e.g., Silver and Pickett 2015) and who are increasingly protective of free speech in a perceived “cancel culture” (e.g., Fahey, Roberts, and Utych 2023)—focused on the nature of the government intervention rather than the protest cause in evaluating the incidents. Along these lines, regarding support for police repression, conservatives may have been more likely than liberals to believe that the broader social system and its representatives (e.g., police) are just and that the repression of protests by police is justified to maintain social order (Goff et al 2022; Silver 2020; Silver, Goff, and Iceland 2022). Another possibility is that conservatives were less likely to view police presence as a form of repression, perhaps because policing of right-leaning protests is often less harsh than policing of left-leaning protests (e.g., Jackson 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies suggest that violence by protesters reduces the perceived legitimacy of, and identification with, protest movements (e.g., Chenoweth, Stephan, and Stephan 2011; Edwards and Arnon 2021; Feinberg et al 2020; Huff and Kruszewska 2016; Simpson, Willer, and Feinberg 2018; Thomas and Louis 2014; but see Shuman et al 2022). Violence may also play a role in shaping support for government repression of protest movements (Edwards and Arnon 2021; Goff et al 2022; Metcalfe and Pickett 2022). Defined by social movement scholars as “any action by another group which raises the contender’s cost of collective action” (Tilly 1978:100), repression may include “law-and-order” policing of protesters (e.g., Goff et al 2022), legal bans on protest activities (e.g., Davenport 2007), or punishing individuals who engage in protests (e.g., Barkan 2006), among other responses.…”
Section: Public Responses To Protest Violence and Harmmentioning
confidence: 99%
See 2 more Smart Citations
“…The nature and clarity of such relationships are underexplored within the literature, yet logical assumptions can be made (Irons, 2006). One such assumption is there are no neutral or disinterested parties during interactions between social and countermovements (Goff et al., 2022). Wood (2019) found that police consistently and disproportionately arrest left‐wing and anti‐racism protesters compared to right‐wing protestors.…”
Section: Blue Lives Matter As a Countermovementmentioning
confidence: 99%